Exercise for your good Health - Pongsiam, Duangpong (Journal of Advanced Development in Engineering and Science, 2023)
From the state now the civilization grows up both of the economy social scientific progress and the Technology a human is which very much important in country development have to of good quality good life will for is mechanical a pillar to will propel the progress economical growth and the social the one thing that us will can encourage to give people has quality of good life be the exercise for the health when exercise already make a body and hardhearted the power when two this thing has the strength our body will have strong health can study work or live efficiently.